Association of arbuscular mycorrhizal fungi (AMF) with sugarcane plants (Saccharum officinarum) for panela production in Colombia - Wilches Ortiz, Wilmar Alexander; Ramírez Gómez, María Margarita; Pérez Moncada, Urley Adrian; Serralde Ordoñez, Diana Paola; Peñaranda Rolon, Andrea María; Ramírez, Luciano (REVISTA TERRA LATINOAMERICANA, 2019)
Sugarcane crop for panela production in Colombia presents nutritional limitations especially with the low eff iciency of chemical fertilization. The use of arbuscular mycorrhizal fungi (AMF) optimizes fertilization, making it more eff icient and can reduce the application of synthetic fertilizers. The objective of this study was to evaluate the association of AMF with sugarcane plants for panela production in seedling stage. A characterization of soils was carried out in the regions of Cundinamarca and La Hoya del Río Suárez (Boyacá and Santander), characterized as the main sugarcane for panela production in Colombia and it was found that sugarcane plants establish a natural association with the AMF. The predominant AMF were Glomus microcarpum, Glomus fasciculatum, Glomus sinuosum, four morphotypes of Glomus sp., two of Acaulospora sp. and one of Funneliformis sp. The effect of the inoculation with AMF in the seedling stage was evaluated using three varieties of sugarcane widely cultivated in the Hoya del Río Suárez, CC93-7711 (Pierna Bella), CC93-714 and CC93-7510 (Vende Finca). Eleven (T1 to T8 inoculation with different communities of AMF, T9, T10 and T11 correspond to controls with fertilizations of 10, 50 and 100% of chemical fertilization) were evaluated in a randomized complete block design with three replications. Plant height and stem diameter, spore quantif ication and percentage of colonization were evaluated. The results showed that the three varieties responded to the benef icial effect of the plant-HMA association, f inding plants with higher yield with respect to the non-inoculated plants. The varieties CC93-7711 (Pierna Bella) and CC93-7510 (Vende Finca) showed a higher percentage of AMF colonization in response to the inoculation of Glomus sp.